2021
DOI: 10.1080/09603123.2021.1973969
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 exposure and olfactory functions

Abstract: Growing evidence indicates that air pollution can negatively impact cognitive functions. The olfactory system is interesting in this context as it is directly exposed to pollutants and also associated with cognitive functions. The aim of this study was to investigate long-and short-term PM 2.5 exposure in association with olfactory functions. Scores from odor tests were obtained from the Betula project -a longitudinal cohort study. Estimates of annual mean PM 2.5 concentrations at the participants' residential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…It has been proposed that the acute, toxic effects of inflammation following short-term air pollution exposure, such as one's average daily exposure, may lead to telomere lengthening by the activation of the enzyme telomerase (27). In the present study we find it unlikely that short-term exposure would influence the results however, since we have previously seen that the correlation between short-term levels and long-term exposure is very low in the Betula study (28).…”
Section: Discussioncontrasting
confidence: 60%
“…It has been proposed that the acute, toxic effects of inflammation following short-term air pollution exposure, such as one's average daily exposure, may lead to telomere lengthening by the activation of the enzyme telomerase (27). In the present study we find it unlikely that short-term exposure would influence the results however, since we have previously seen that the correlation between short-term levels and long-term exposure is very low in the Betula study (28).…”
Section: Discussioncontrasting
confidence: 60%
“…Thus, one possible explanation to our results is that pollution independently is associated with risk of dementia, and declining olfactory function. However, a previous study using the Betula cohort [ 17 ] concluded that air pollution had no detrimental effects on olfactory functions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 16 ] found associations between air pollution and decline in odor identification ability, in an area with relatively low levels of pollution. However, a previous study also using data from the Betula Project [ 17 ] found no associations between air pollution and olfactory functions.…”
Section: Introductionmentioning
confidence: 93%
“…While particulate matter is not directly related to bad odours, as it is seemingly odourless, it may be associated with sources (industrial or agricultural) that produce bad odours. However, relevant research provides evidence of a positive association between long-term PM 2.5 exposure and odour identification [22]. Furthermore, sulphur dioxide is a gas with a strong, irritating and pungent odour used in a variety of workplaces (i.e., in inorganic and petrochemical industries) [23], making it an ideal choice for the needs of our research.…”
Section: Data Pre-processingmentioning
confidence: 99%